BISSU; KEPERCAYAAN, KELAKUAN DAN KEWARGANEGARAAN - Feby Triadi (Kementerian Pendidikan dan Kebudayaan, 2020)
This paper wants to trace the presence of the country in guaranteeing the trust of its citizens to worship the Almighty God. After the presence of government regulations regarding the recognition of the flow of belief can be stated on the Identity Card (KTP), in fact, this regulation only recognizes certain beliefs. So the choice to leave the option in the column of religion is considered accurate, instead of solving the problem, the emptying is considered to be more clear if the believer does not get recognition from the state. This research was conducted in South Sulawesi, in January 2019. With the context of bissu as an adherent of the belief flow of the attoriolong, the participatory observation data collection method was used. The data obtained will be processed using Spradley's (1980) analysis technique. The names used in this paper are pseudonyms, to fulfill ethics, and research strategies. This study found that the bissu community which had nine institutions was not identified as a belief, this was due to the strong influence of the developing Islam. Also exacerbated is the definition of a highly sectarian religious definition by the state, further prolonging the polemic of the identity of beliefs for bissu.